(untitled) (REMUNOM, 2025)
Discussions on epistemology have traversed the entire philosophical tradition, establishing themselves as one of the most complex and enduring themes of philosophical reflection. In modernity, this issue acquires special relevance, becoming the central axis of investigations into the sources, limits, and justification of human knowledge. Various thinkers sought to establish reliable criteria capable of distinguishing truth from falsehood, proposing methodologies of foundation that could ensure the validity and rational certainty of knowledge. This work aims to examine the problem of the justification of knowledge, initially taking as a reference the methodology of foundation based on sufficient reasons, which seeks to sustain the possibility of absolute and universal truths. This conception, however, will be contrasted with the proposal of Karl Popper, developed within the framework of critical rationalism, according to which human knowledge is essentially conjectural, provisional, and subject to refutation. From this perspective, knowledge does not depend on indubitable foundations but advances through criticism and the correction of errors, constituting a rational and dynamic process.